Diversication advantages during the global financial crisis - Mats Levander (Sveriges Riksbank, 2018)
In this paper, I investigate whether being part of a business group mitigated the effects of the global financial crisis for Swedish firms. The crisis is used as an exogenous shock to firms' external financing. The investments made by business group firms are compared to those made by standalone firms. I find that being part of a business group had a mitigating effect on the impact of the crisis on firm investments. Firms that were part of a business group reduced their investments by significantly less than standalone firms. These differences are driven by a diversification effect among business group firms due to the use of internal capital markets and easier access to external financing. I present evidence of increased internal capital market activity during the crisis. Finally, my results suggest that business group firms profitability increased relative to the profitability of standalone firms after the crisis.
Keywords: G01; G30; G32; 330; Financial crisis; firm investment; business group; internal capital markets; external financing constraints